The Experiences of Mothers Giving Birth with Tohu Danga's Assistance in Indragiri Hulu Regency - Sari Ndraha, Piki Nadia; Purwarini, Justina; Anggraeni, Lina Dewi (Fakultas Ilmu-ilmu Kesehatan, 2024)
Tohu Danga are believed to be maternity assistants who care for women and infants before and after birth. This study aimed to explore the experiences of women in the Indragiri Hulu Regency who gave birth with the assistance of Tohu Danga. This study used a descriptive phenomenological approach with a total of 12 women. Participants were obtained by the snowball method until data saturation was reached. Data was collected through in-depth interviews. The Colaizzi analysis technique was used. The findings of this study generated six themes: (1) the significance of childbirth for women who give birth with Tohu Danga, (2) the context that determines the women's choice of birth attendant, (3) the cultural practice of Tohu Danga's birth aid, (4) the difficulty of the longer birth process, (5) the relationship between Tohu Danga birth care and traditional medicine, and (6) the positive and negative responses of women regarding the birth process with Tohu Danga. Nurses are forced to think critically when a woman's cultural practices can affect health and provide nursing care according to their patient’s cultural requirements.